Exosomes populate the cerebrospinal fluid of preterm infants with post-haemorrhagic hydrocephalus. Issue 73 (April 2019) - Spaull, Robert; McPherson, Bryony; Gialeli, Andriana; Clayton, Aled; Uney, James; Heep, Axel; Cordero-Llana, Óscar
Graphical abstract: Highlights: Exosomes populate the cerebrospinal fluid of preterm infants with post-haemorrhagic hydrocephalus. Exosomes found after intraventricular hemorrhage are from serum and brain. Micro-RNAs isolated from the exosomal fraction relate to development and disease. Abstract: Background: Preterm infants are at risk of germinal matrix haemorrhage-intraventricular haemorrhage (GMH-IVH) which leads to post-haemorrhagic hydrocephalus (PHH) in 30% of infants; this is associated with moderate-severe neurodevelopmental impairment and confers significant risk of cerebral palsy. There are however no predictive indicators of the severity or long-term outcome after GMH-IVH. In recent years, endosome-derived extracellular vesicles (EVs) or exosomes have been isolated from biofluids and shown to mediate intercellular communication via selective enrichment in proteins and micro-RNAs. Methods: This study aimed to isolate and characterise EVs from the cerebrospinal fluid (CSF) of 3 preterm infants with PHH using nanoparticle tracking analysis (NTA), transmission electron microscopy (TEM) with immunogold protein labelling, and micro-RNA analysis. Results: NTA of unaltered CSF revealed a heterogeneous and dynamic population of EVs. Exosomal-sized EVs were isolated by differential ultracentrifugation and TEM confirmed the presence of CD63 + and CD81 + exosomes. The micro-RNAs miR-9, miR-17, miR-26a, miR-124 and miR-1911 were detected within the exosome-enriched fraction and profiled over time. Conclusion: This is the first reported characterisation of exosomes from the CSF of preterm infants with post-haemorrhagic hydrocephalus.